Brand Name Language: Is it True That Foreign Brand Names are More Qualified, Luxurious and Modern? - Sutisna, Sutisna; Rustandi, Tata (International Review of Management and Marketing, 2023)
The purpose of this study is to see whether product brand names that use foreign languages, especially English, are perceived as higher quality, more luxurious, and more modern than product brand names that use local languages by consumers in developing countries. The population in this study were residents of Banten Province, Indonesia. Data collection using a questionnaire distributed via google form and collected as many as 275 respondents’ answers. The analysis method uses paired sample mean difference test. The results showed that foreign brand names that use foreign languages are perceived as higher quality, more luxurious, and more modern than brand names that use local languages. Therefore, giving product brand names whose markets are consumers in developing countries, using foreign language brand names, especially English, will be preferred by consumers.